Treatment of Cutting Oil-in-Water Emulsion Using Electrocoagulation - Alireza Nazari Alavi; Shahnaz Ghasemi (آب و فاضلاب, 2023)
Cutting oils are used in machining operations to reduce friction, provide lubrication and cooling properties, and prevent corrosion. Biological methods for treating wastewater from these oils have low efficiency. Therefore, other methods should be considered to treat this type of wastewater. The purpose of this study was to investigate the use of electrocoagulation for treatment of wastewater containing cutting oil. In this regard, an electrochemical reactor equipped with two aluminum electrodes and a direct power source was used. The efficiency of the electrocoagulation process was evaluated by measuring the removal percentage of chemical oxygen demand in a certain time range. The effect of various operating parameters such as oil concentration, applied voltage, stirring speed, initial pH, distance, and surface of electrodes on the efficiency of the electrocoagulation process was investigated. The results of the experiments showed that reducing the oil concentration from 3% by volume to 0.5% by volume led to an increase in the efficiency of the purification process up to 97.3%. Increasing the voltage from 40V to 60V reduced the time required for wastewater treatment with the same efficiency from 50 min to 20 min. Decreasing the distance between the electrodes from 6 cm to 2 cm and increasing the effective area of the electrodes from 60 cm2 to 180 cm2 reduced the time required for purification to 20 min. Also, the results of the tests showed that the time required for the purification process at medium stirring speeds (150 rpm) is low. The obtained results showed that the removal percentage of chemical oxygen demand in the neutral environment was high (95.9%). Therefore, due to the simplicity of the method, low operating cost, and the ability to design on an industrial scale, the electrocoagulation method can be used for the treatment of wastewater containing cutting oil.